Sacralizing the nation through remembrance of medieval religious figures in Serbia, Bulgaria and Macedonia. [Volume 1] - Rohdewald, Stefan, 1972-; Barnwell, Tim (Leiden : Brill, 2022)
Religious figures of remembrance served to consolidate first dynastic rule and later nation-state legitimacy and community. This book explains the interweaving of (Eastern) Roman, medieval Serbian and Bulgarian contexts as well as Ottoman and Western European national discourses or reinvented traditions. We can distinguish a secularization and nationalization of the religious contexts in the 19th century within historicism, followed by a nationalization of God and a sacralization of the nation until the end of WWII. Contrary to the national views, the origins of the modern content of these discourses lie only to a very limited extent in the Middle Ages or in the Early Modern period, as this study shows.
1, Introduction -- 2, Holy teachers, rulers, and capitals - religious memory-figures up to the 18th century -- 3, The Invention of european, christian nations to overcome the "asian yoke" in the long 19th century
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: jižní Slované; národní identita -- Balkánský poloostrov; pravoslavné církve -- Balkánský poloostrov; patroni -- Balkánský poloostrov; vzpomínková kultura -- Balkánský poloostrov; Southern Slavs; national identity -- Balkan Peninsula; Orthodox Eastern churches -- Balkan Peninsula; Christian patron saints -- Balkan Peninsula; culture of remembrance -- Balkan Peninsula; Balkánský poloostrov -- náboženské a kulturní poměry; Evropa západní -- náboženské a kulturní poměry; Balkan Peninsula -- religious and cultural conditions; Europe, Western -- religious and cultural conditions; e-knihy online; monografie; e-books online; monographs